Blaan Farming Rituals, Reconciliation, and Punitive Practices in Pangyan as Basis for Play Development - Yama, Janevic (International Journal of Arts, Sciences and Education, 2025)
This study aims to explore and analyze the rituals of the Blaan people in Pangyan, Sarangani Province, using a descriptive-qualitative approach. The collected data was examined to gain insights into the significance of these rituals within their culture, beliefs, and daily life. Three key rituals were explored: the Damso related to farming, the Sadyandi for reconciliation, and the Sulif used in punishment. Each ritual has a distinct process and symbolism, reflecting the Blaan’s deep connection to spirituality and nature. To further enhance the understanding and appreciation of these practices, a play was created based on the findings and subjected to expert validation. The results showed that the play was highly effective and well-received, proving its potential as a powerful medium for introducing, preserving, and promoting Blaan cultural heritage. However, the study also highlighted a concerning trend: these traditional rituals are gradually fading away due to modernization and changes in the justice system. In light of this, the study recommends strengthening efforts to protect and document these rituals, ensuring that the cultural wealth of the Blaan people is preserved for future generations. This research emphasizes the importance of maintaining cultural traditions while adapting to modern influences, ensuring that the Blaan people’s heritage continues to thrive.